Late holocene benthic Foraminifera of the Roman Lacus ligustinus (SW Spain): a paleoenvironmental approach - Guerra, Liliana (2021)
This paper studies the Late Holocene benthic foraminifera from a continuous core extracted in the Doliana National Park (SW Spain). In this core, the foraminiferal assemblages confirm the Late Holocene lagoon (historically so-called Locus Ligustinus) during the Roman period, about 2000 years ago. The more open, deepest areas of this lagoon were dominated by Ammonia tepida and Elphidium spp., while Haynesina germanise was the most representative species of the shallow, more restricted zones. The vertical variations of these assemblages, together with associated sedimentological and macrofaunal changes, allow recognizing three high-energy events (HEE) between 500 BCE and 500 CE, which also left an extensive sedimentary record in nearby coastal areas: two tsunamis (HEE-1 and HEE-3) and a storminess period (HEE-2).